2014
DOI: 10.4236/oalib.1101049
|View full text |Cite
|
Sign up to set email alerts
|

Flowering and Seed Development in Onion—A Review

Abstract: Proper vernalization temperature of mother onion bulbs stimulates early flowering and produces a heavier yield of seed. Moreover, onion cultivars seem to differ in their optimal temperature requirements depending on the locality to which they are adapted. Most studies on the effects of storage temperature on inflorescence initiation in onion have shown that the optimum temperature for flowering is in a range between 5˚C to 13˚C for 90 to 120 days and bolting resistant varieties require a longer cold stimulus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 49 publications
0
16
0
10
Order By: Relevance
“…Early attempts at vernalizing seedlings were met with mixed results until the discovery that seedlings must pass a juvenile phase before they are receptive to chilling (Holdsworth and Heath, 1950). The juvenile phase is cultivar dependent and can range from the 4-to 14-leaf stage, after which the plants are vernalized for %60 d (Khokhar, 2014;Rabinowitch, 1985;Shishido and Saito, 1976). Although seedling vernalization is a useful tactic for producing seed rapidly, and it has applications in marker-assisted selection and backcrossing, there are limitations for its use in phenotypic selection of bulb traits because this procedure does not allow for evaluation of the mature bulb.…”
mentioning
confidence: 99%
“…Early attempts at vernalizing seedlings were met with mixed results until the discovery that seedlings must pass a juvenile phase before they are receptive to chilling (Holdsworth and Heath, 1950). The juvenile phase is cultivar dependent and can range from the 4-to 14-leaf stage, after which the plants are vernalized for %60 d (Khokhar, 2014;Rabinowitch, 1985;Shishido and Saito, 1976). Although seedling vernalization is a useful tactic for producing seed rapidly, and it has applications in marker-assisted selection and backcrossing, there are limitations for its use in phenotypic selection of bulb traits because this procedure does not allow for evaluation of the mature bulb.…”
mentioning
confidence: 99%
“…Seed production plays a key role in onion cultivation and is a highly specialized activity requiring special knowledge (Khokhar, 2014). According to the results of our surveys, only a few producers specialized in the production of onion seeds.…”
Section: Agricultural Inputs Seed Productionmentioning
confidence: 91%
“…Thus, it has been shown that storage temperatures ranging from 7˚C to 12˚C induce flowering earlier than the lowest or highest temperatures (Jones andEmsweller, 1939 andJones, 1927). In a literature review, it was concluded that onion cultivars appear to differ somewhat in their optimal temperature requirements depending on the locality to which they are adapted (Khokhar, 2014). The best yield of onion seeds is obtained with large bulbs (Morozowska and Holubowicz, 2009; Aminpour and Mortazavibak, 2004).…”
Section: Agricultural Inputs Seed Productionmentioning
confidence: 99%
“…1) and this variation in terminal heat condition greatly influenced the seed development and production. Olani Nikus and Fikre Mulugeta (2010) and Khokhar (2014) had reported that temperature ranges between 4.5-14 o C with low humidity is favorable for seed stalk formation. If this type of temperature prevails for longer periods then each plant will produce more number of flowers in each umbel.…”
Section: Productivitymentioning
confidence: 99%